A Corpus-based Approach to Lexical Semantics in the French Version of the 2015 ITUC Rights Index - AKPACA, SERVAIS MARTIAL (My University, 2015)
This paper studies the lexical fields of the words ''labour'', ''employment'', ''work'', ''job'' and ''membership'' in the French version of a labour-related corpus. Its aim is to demonstrate that there is no perfect fit between words in English and French. Indeed, the word labour, for example, has been translated by the words ''travail'', ''main-d'oeuvre'', ''travailleurs'' in the French version. It takes a lexical field made up of all these French words to translate the lexical item ''labour''. Therefore, concepts are not universal because each language articulates reality in its own manner.
Keywords: Lexical item; lexical field; lexeme; concept; conceptual field; semantics